Al-Qur'an dan Filsafat Ilmu Pengetahuan: Studi Pemikiran Nidhal Guessoum - Qowim Musthofa (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2021)
The Qur'an is not a text of science, although in general scientific facts (phenomena of nature) are mentioned in it. It's just that in the era of the revelation of the Qur'an 17th century, the development of science is not like today. Hence the contemporary Muslim intellectuals to prove over the miracle of the Qur'an that actually contain the philosophy of knowledge that is very influential in the development of modern science. Various approaches have been used in order to give new meaning to the text of the Qur'an is static-limited with scientific approaches that are active-dynamic. One of them with hermeneutics to reread and reinterpret the text of the Qur’an to revive the text of the Qur'an itself.